2016
DOI: 10.1002/jso.24146
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the safety and efficacy of full robotic gastrectomy with intracorporeal robot-sewn anastomosis for gastric cancer: A randomized clinical trial

Abstract: Full robotic gastrectomy with intracorporeal robot-sewn anastomosis for gastric cancer is safe and does not increase the complication risk during or after surgery. J. Surg. Oncol. 2016;113:397-404. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 47 publications
2
51
1
Order By: Relevance
“…The full text of the remaining 23 articles were reviewed; of these, 1 was excluded because it was a redundant and lower level series, 11 contained non relevant topics, 5 because it was impossible to retrieve or calculate data of interest. Finally, a total of 6 articles[21-26] (South Korea 2, China 2, Italy 1, Romania 1) were considered eligible for inclusion in the meta-analysis (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…The full text of the remaining 23 articles were reviewed; of these, 1 was excluded because it was a redundant and lower level series, 11 contained non relevant topics, 5 because it was impossible to retrieve or calculate data of interest. Finally, a total of 6 articles[21-26] (South Korea 2, China 2, Italy 1, Romania 1) were considered eligible for inclusion in the meta-analysis (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…The results of a single-center prospective randomized trial were reported by Wang et al (47) They randomized a total of 311 patients to either open (n=153) or robotic (n=158) gastrectomy groups by the envelope method. They showed similar complication rates between the groups, and less estimated blood loss, longer duration of surgery, and shorter postoperative hospital stay in the robotic group than open group.…”
Section: Prospective Studiesmentioning
confidence: 99%
“…Recently, Wang et al reported a single-center randomized clinical trial for robotic gastrectomy compared with open gastrectomy [13]. This report showed that robotic gastrectomy group had less blood loss (94.2 ± 51.5 versus 152.8 ± 76.9 ml, p < .001), a shorter hospital stay (5.6 ± 1.9 versus 6.7 ± 1.9 days, p = .021), and earlier recovery of bowel function (2.6 ± 1.1 versus 3.1 ± 1.2 days, p = .028), but a longer operation time (242.7 ± 43.8 versus 192.4 ± 31.5 min, p = .002), than the open gastrectomy group.…”
Section: Overview and Historymentioning
confidence: 99%
“…Compared with open gastrectomy, robotic gastrectomy had a shorter length of postoperative hospital stay [10, 13]. However, most studies showed no difference in length of hospital stay when comparing robotic and laparoscopic gastrectomies.…”
Section: Issues Regarding Robotic Gastrectomymentioning
confidence: 99%
See 1 more Smart Citation